The Influences of Compensation and Commitment of Organizaiton Toward Employes' Performance - Evelyn Nadapdap; Nainggolan, Vera Rianty; Nemia Manalu; Lastari Simbolon (ASIAN PUBLISHER, 2023)
This study aims to determine the effect of compensation and organizational commitment on employee performance. research shows that: 1) Compensation and Organizational Commitment simultaneously have a significant effect on employee performance, 2) Compensation and Organizational Commitment partially have a significant effect on employee performance, 3) Organizational Commitment Variable is a variable that influences employee performance